U-Pb geochronology of detrital zircon crystals from Caratas and Los Arroyos formations, Northeastern Venezuela. - Noguera, Mariela; Wright, James; Urbani, Franco; Pindell, James (Rev. Téc. Fac. Ing. Univ. Zulia, 2014)
Â LA-MC-ICPMS U-Pb geochronology in detrital zircons was performed in two Tertiary turbidite sequences from Northeastern Venezuela to contribute to the understanding of the Cenozoic history of the northern South America plate. The age results of detrital zircons from the Eocene Caratas Formation show a range of Late Archean to Middle Proterozoic ages, suggesting a unique source from a drainage coming from the southern Guayana Shield. The Middle-Miocene turbidite of Los Arroyos Formation displays a detrital zircon age signature from Paleoproterozoic to Silurian which is significantly similar to an Early Cretaceous passive margin unit. The Guayana Shield has long been interpreted as the source of siliciclastic detritus within the Cretaceous passive margin and Tertiary strata of northern Venezuela; these ideas are compatible with our results that confirm previous models of Caratas and Los Arroyos formations as deposited in marine intracontinental basins with no influence of rock units from the Caribbean realm.